Market Reaction to the Covid-19 Pandemic: Evidence from Countries in the Asia Pacific - Indah Yuliana; M. Muzanni (International Journal of Social Science and Business, 2023)
The covid-19 pandemic spread rapidly in the Asia Pacific region, causing economic losses, exacerbating market volatility, and disrupting economic chains in Asia Pacific countries. This study aims to analyze the differences in capital market reactions before and after the announcement of covid-19 in the Asia Pacific Region. This study uses an event study approach using a variable stock price index, return, trading volume, and exchange rate.  The research sample was 11 stock exchanges in Asia Pacific countries with purposive sampling techniques.  Data testing using the data normality test and two average difference tests using a Paired Sample T-Test for normally distributed data and the Wilcoxon Singed Rank-Test test for data that is not normally distributed. The results showed that (1) there are differences in stock price indices before and after the announcement of covid-19 cases in Indonesia, Malaysia, Singapore, Mexico, Taiwan, Hong Kong, and New Zealand. Meanwhile, Thailand, Australia, Japan, and South Korea showed no differences. (2) there are differences in returns during covid-19 cases in Malaysia and Taiwan. While Indonesia, Singapore, Thailand, Australia, Japan, South Korea, New Zealand, Mexico, and Hong Kong showed no difference. (3) There are differences in stock trading volumes during covid-19 cases in Malaysia, Australia, Mexico, and Hong Kong. Meanwhile, Indonesia, Singapore, Thailand, Japan, South Korea, New Zealand, and Taiwan showed no difference. (4) There are differences in exchange rates during covid-19 cases in Indonesia, Malaysia, Singapore, Thailand, Australia, South Korea, New Zealand, Taiwan, and Hong Kong. While in Japan, it shows no difference.